Partitioning Ocean Motions Into Balanced Motions and Internal Gravity Waves: A Modeling Study in Anticipation of Future Space Missions. Issue 11 (9th November 2018) - Torres, Hector S.; Klein, Patrice; Menemenlis, Dimitris; Qiu, Bo; Su, Zhan; Wang, Jinbo; Chen, Shuiming; Fu, Lee‐Lueng
Abstract: Internal gravity waves (IGWs) and balanced motions (BMs) with scales <100‐km capture most of the vertical velocity field in the upper ocean. They have, however, different impacts on the ocean energy budget, which explains the need to partition motions into BMs and IGWs. One way is to exploit the synergy of using different satellite observations, the only observations with global coverage, and a reasonable spatial and temporal resolution. But we need first to characterize and understand their signatures on the different surface oceanic fields. This study addresses this issue by using an ocean global numerical simulation with high‐resolution (1/48°). Our methodology is based on the analysis of the 12, 000 frequency‐wave number spectra to discriminate these two classes of motions in the surface kinetic energy, sea surface height, sea surface temperature, sea surface salinity, relative vorticity, and divergence fields and for two seasons. Results reveal a complex picture worldwide of the partition of motions between IGWs and BMs in the different surface fields, depending on the season, the hemisphere, and low and high eddy kinetic energy regions. But they also highlight some generic properties on the impact of these two classes of motions on the different fields. This points to the synergy of using present and future satellite observations to assess the ocean kinetic energy on a global scale. The 12, 000 frequency‐wave number spectra represent a World Ocean Atlas of the surface ocean dynamics not fully exploited in the present study. We hope the use of this World Ocean Atlas by other studies will lead to extend much these results. Plain Language Summary: Motivation of partitioning surface oceanic motions with scales <100 km into two classes, balanced motions (BMs) and internal gravity waves (IGWs), is that they are known to have different impacts on the ocean kinetic budget although they share the same range of spatial and temporal scales. Satellite observations are the only ones with a global coverage to capture oceanic surface motions. Our motivation of exploiting the synergy of using all these observations is that these two classes of motions can have different signatures on each of these observations. The results reveal a complex picture worldwide of the partition of motions between IGWs and BMs in the different surface fields, depending on the season, the hemisphere, and low and high eddy kinetic energy regions. But they also highlight some generic properties on the impact of these two classes of motions on the different fields. This emphasizes the strong synergy of using present and future satellite observations to diagnose this partition on a global scale. The results can be of interest for Earth Science community because of their consequences on the ocean kinetic energy budget, the physical‐biological interactions, and the air‐sea interactions. Key Points: The respective signature of balanced motions and internal gravity waves on different surface oceanic fields has been revealed The World Ocean reveal a complex picture worldwide of the partition of motions between balanced motions and internal gravity waves The synergy of using present and future satellite observations can be exploited to assess the oceanic kinetic energy on a global scale